2000
DOI: 10.1063/1.1289268
|View full text |Cite
|
Sign up to set email alerts
|

Acceptor reactivation kinetics in heavily carbon-doped GaAs epitaxial layers

Abstract: The reactivation kinetics of the acceptor behavior of carbon in GaAs layers has been studied. The reactivation was achieved by ex situ rapid thermal annealing. To follow the carbon reactivation process, a multistage annealing experiment was performed, with changes in the sample carrier concentration monitored at each stage. An analysis of these data indicates that carbon reactivation follows a first-order kinetics process that can be explained by a model which includes the effects of dopant repassivation by hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 16 publications
0
16
0
1
Order By: Relevance
“…Probably, carbon is also incorporated at interstitial sites or on element III positions. Interstitial carbon could act as scattering centers and would give a decrease of the hole mobility [5]. Indeed, it was found that the hole mobility at similar carrier concentrations decreases with increasing T G [39].…”
Section: Hydrogen Incorporationmentioning
confidence: 99%
See 1 more Smart Citation
“…Probably, carbon is also incorporated at interstitial sites or on element III positions. Interstitial carbon could act as scattering centers and would give a decrease of the hole mobility [5]. Indeed, it was found that the hole mobility at similar carrier concentrations decreases with increasing T G [39].…”
Section: Hydrogen Incorporationmentioning
confidence: 99%
“…In the past few years, the development of new doping methods [3], better control of the doping level [4] and new insights in the reactivation of carbon [5,6] have further improved its suitability as a way of obtaining p-type doped layers in devices [7,8]. A common way of carbon doping in Al x Ga 1Àx As (x40) is the use of an independent carbon precursor such as carbon tetrachloride (CCl 4 ) [9] and carbon tetrabromide (CBr 4 ) [10].…”
Section: Introductionmentioning
confidence: 99%
“…Разработка новых методов легирования [12], включа-ющих точный контроль уровня легирования [13] и новые способы реактивации примесей [14,15], привела к значи-тельному улучшению качества эпитаксиальных слоев и, как следствие, расширила сферу их применения [16,17]. Основными легирующими примесями в A III B V являются углерод и кремний.…”
Section: Introductionunclassified
“…However, heavy carbon doping over 10 19 cm À3 by metal-organic chemical vapor deposition (MOCVD) incorporates large amounts of hydrogen atoms in the base layer [3,4]. The presence of hydrogen atoms affects the device performance [5][6][7][8][9][10][11]. The current gain increases and stabilizes after a current injection for a few seconds, which is called short-term gain-drift [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%